Agricultural diversification in India and role of urbanization - Rao, P. Parthasarathy; Birthal, Pratap Singh; Joshi, Pramod Kumar; Kar, D. (International Food Policy Research Institute, 2004)
Indian agriculture is diversifying during the last two decades towards High-Value Commodities (HVCs) i.e., fruits, vegetables, milk, meat, and fish products. The pace has been accelerated during the decade of 1990s. HVCs account for a large share in the total value of agricultural production. Supply and demand side factors coupled with infrastructural development and innovative institutions drive these changes. In this paper, the focus is on diversification towards HVCs in the context of urbanization. Group of urban districts (districts with >1.5 million urban population) have a higher share of HVCs compared to the urban-surrounded (near urban districts) and other districts (districts in the hinterland). Among the HVCs, vegetables and meat products have a higher share in urban districts compared to the other two groups. Milk production is more widespread due to excellent network of co-operatives and infrastructure facilities. Using GIS (geographic Information System) approach it was found that urban-surrounded districts with better road network connection to urban centers have been able to diversify towards HVC’s to meet the demand in the urban centers. Model results further confirm these findings. Thus, urbanization is a strong demand side driver promoting HVCs. Since urban population is growing at more than 3% per annum, demand for HVCs will drive their production. The analysis has also brought out regional variations in HVCs across different districts in the country that has implications on regional development and planning, and consequently on public and private sector investment strategies.